Effect of “DXB-2030,” a Polyherbal Formulation, on Experimental Polycystic Ovary Syndrome Associated with Hyperandrogenism - Mohammed Azeemuddin; Suryakanth D. Anturlikar; Mallappa Onkaramurthy; Mirza R. Baig; Basti K. Ashok; Raghavendra P. Rao; Mohamed Rafiq; Paramesh Rangesh (Advances in Pharmacological Sciences)
The objective of the present study was to evaluate “DXB-2030,” a polyherbal combination of Trigonella foenum-graecum, Aloe vera, Sphaeranthus indicus, Nardostachys jatamansi, and Symplocos racemosa extracts in an experimental model of testosterone propionate (TP), induced polycystic ovary syndrome (PCOS) in female rats. Thirty animals were divided into 3 groups of 10 each; group 1 served as normal control; group 2 was administered with TP and served as positive control; along with TP, group 3 was treated with “DXB-2030” at a dose of 100 mg/kg p.o., for 60 days. At the end of the study period, the animals were subjected for the estimation of serum testosterone levels, oral glucose tolerance test (OGTT), weight of the ovaries, estrous cycle, and histopathological evaluation. An in vitro assay on GLUT4 expression was carried out to understand the effect of “DXB-2030” on insulin resistance. Results showed that treatment with “DXB-2030” reversed the TP-induced changes by increasing the GLUT4 expression and decreasing the body weight, testosterone levels, AUC of glucose in OGTT, and the cystic follicles of the ovaries, thus indicating its beneficial effect in PCOS by ameliorating the metabolic dysfunction and reproductive impairment, which are the pathophysiological conditions associated with PCOS. From the results obtained, it can be concluded that “DXB-2030” was effective in the management of experimental PCOS and hence may be recommended in the treatment of PCOS.